Twisted thinking: Technology, values and critical thinking. (1st June 2022) - Marin, Lavinia; Steinert, Steffen
Abstract : Technology should be aligned with our values. We make the case that attempts to align emerging technologies with our values should reflect critically on these values. Critical thinking seems like a natural starting point for the critical assessment of our values. However, extant conceptualizations of critical thinking carve out no space for the critical scrutiny of values. We will argue that we need critical thinking that focuses on values instead of taking them as unexamined starting points. In order to play a crucial role in helping to align values and technology, critical thinking needs to be modified and refocused on values. Here, we outline what value-centred critical thinking could look like.